Smad4 regulates growth plate matrix production and chondrocyte polarity - Whitaker, Amanda T. (Biol Open, 2017)
Smad4 is an intracellular effector of the TGFβ family that has been implicated in Myhre syndrome, a skeletal dysplasia characterized by short stature, brachydactyly and stiff joints. The TGFβ pathway also plays a critical role in the development, organization and proliferation of the growth plate, although the exact mechanisms remain unclear. Skeletal phenotypes in Myhre syndrome overlap with processes regulated by the TGFβ pathway, including organization and proliferation of the growth plate and polarity of the chondrocyte. We used in vitro and in vivo models of Smad4 deficiency in chondrocytes to test the hypothesis that deregulated TGFβ signaling leads to aberrant extracellular matrix production and loss of chondrocyte polarity. Specifically, we evaluated growth plate chondrocyte polarity in tibiae of Col2-Cre(+/−);Smad4(fl/fl) mice and in chondrocyte pellet cultures. In vitro and in vivo, Smad4 deficiency decreased aggrecan expression and increased MMP13 expression. Smad4 deficiency disrupted the balance of cartilage matrix synthesis and degradation, even though the sequential expression of growth plate chondrocyte markers was intact. Chondrocytes in Smad4-deficient growth plates also showed evidence of polarity defects, with impaired proliferation and ability to undergo the characteristic changes in shape, size and orientation as they differentiated from resting to hypertrophic chondrocytes. Therefore, we show that Smad4 controls chondrocyte proliferation, orientation, and hypertrophy and is important in regulating the extracellular matrix composition of the growth plate.